Knowing the Self Through Fantasy: Toward a Mytho-poetic View of Transformative Learning - John M. Dirkx (Adult Education Research Conference, 1998)
Research suggests that adult learning can have a profound effect on our sense of self. Emergence of transformational theory provides a framework for understanding these processes of self-knowing. Yet, this research and theory is dominated by an heroic perspective, in which transformation results from hard effort of a rational ego. Relying on a philosophy of imagination and Jungian psychology, transformative learning is re-visioned here as a journey of soul, in which image and fantasy mediate processes of self-knowing.